The Logical Relationship between Religion and Applied Sciences: A Critical Book Review - Malek Shojaei Jeshvaghani; Seyyed Mohammadtaghi Movahhed Abtahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Although more than two decades have passed since the publication of the first edition of The Logical Relationship between Religion and Applied Sciences, this book is still one of the most coherent and accurate works, showing the position of this intellectual current. The author of the book has tried to show the position of the Academy of Islamic Sciences on these issues, considering the academic literature on topics such as science, technology, and development. So, this book was regarded for proper introduction and critique. In this article, we have shown that the author of the book does not have much control over the latest controversies in the field of science and religion studies - even in contemporary Iran. Today’s controversy, which has challenged European-Christian hegemony based on the study of science and religion, could open a new space for a different view of the relationship between religion, culture, and technology. Therefore, it is expected that the author will write the second edition of the book, considering the latest achievements of contemporary scientology and theology.